Terapi Doxycycline pada Laki-laki Homoseksual dengan Sifilis Sekunder dan Infeksi Human Immunodeficiency Virus - Anggana Rafika Paramitasari; Imroatul Ulya; Agung Triana Hartati; Susanti Rosmala Dewi; Prasetyadi Mawardi (MEDICINUS, 2021)
Background: Re-emergence of syphilis is increasing especially among MSM (men who have sex with men) patients. Syphilis in HIV-infected patients is reported to show faster and higher risk for progression to neurosyphilis. Co-infection of syphilis and human immunodeficiency virus (HIV) is correlated with decrease in CD4 and increase in HIV-RNA. Doxycycline has an antiinflammatory effect associated with decrease of HIV-RNA and increase of CD4 in HIV patients. Case: A 20 years old foreigner MSM man complained about non-itchy red spots throughout his body for 2 days with slight fever. He has a history of more than 10 sexual partners and rarely use condom. Physical examination revealed various sizes of erythematous macules and papules on his trunk and extremities. We found erythematous plaques with regular border but no ulcer on his scrotum and no secrete from his urethra. There was enlargement in the inguinal lymph node. VDRL and TPHA examinations were 1:32 and 1:640, respectively. HIV test was reactive with CD4 value 558 cells/ml. Treatment consists of doxycycline 2x100 mg for 14 days and also ARV (nevirapine, lamivudine and zidovudine). His symptoms were improved after a month accompanied with decreased VDRL to 1:2 and slightly increased CD4 to 570 cells/ml. Discussion: Doxycycline is a second line treatment for syphilis that is known to help decreasing the viral load and increasing CD4 level in syphilis with HIV. A significant decrease in VDRL titer in this patient indicates a successful therapy.